Development of Soft Skills in Secondary Students at an International School Through Stem+ Library Activities Utilizing Augmented Reality Boards - Teamsakool, Thanchanok; Klinkesorn, Phussadee (Journal of Graduate MCU KhonKaen Campus, 2025)
The purposes of this research were to 1) design and develop STEM Plus Library activities to enhance students’ character skills and 2) examine the effects of the activities after implementation, including 1) comparing students’ character skills with the established criterion of 80 percent and 2) assessing students’ satisfaction with the activities. The sample consisted of 98 Year 7–8 students from an international school, selected through cluster random sampling. The research instruments included 1. STEM Plus Library activity plans, 2. a character skills assessment test, and 3. a satisfaction questionnaire. Data were analyzed using mean, standard deviation, and t-test. The results indicated that 1) the STEM Plus Library activity plans were rated at the highest level of appropriateness ( = 4.58, S.D. = 0.49) 2) students’ character skills after participating in the activities were significantly higher than the criterion at the .05 level. In addition, students reported the highest level of satisfaction with the activities ( = 4.69)